2007
DOI: 10.1097/mlg.0b013e3180959e1e
|View full text |Cite
|
Sign up to set email alerts
|

Postallograft Donor and Recipient Dendritic Cell Trafficking in the Rat Larynx

Abstract: The paradigm of donor DC efflux and recipient DC influx has been confirmed in a rat laryngeal transplant model, and the allograft-specific timing of these events has been elucidated. Similarities in total DC migration between allografts and isografts suggest that this phenomenon may not be driven entirely by major histocompatibility mismatch. Further understanding of trafficking may help with the goal of manipulating DC to induce allograft tolerance in the absence of generalized immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The length of cold ischaemia in this study (340 min) is between that in the only two reported human laryngeal transplants: At 48 h, we observed a small decrease in expression of MHC-II and lymphocyte-associated molecules, while there was a small increase in other myeloid-associated molecules. This is consistent with the observations of Friedman et al [23] using heterotopic grafts in rats, where separate labelling of donor and recipient cells suggested depletion of donor leucocytes from the graft before the appearance of recipient cells.…”
Section: Quantitative Immunofluorescence Immunohistochemistrysupporting
confidence: 93%
See 3 more Smart Citations
“…The length of cold ischaemia in this study (340 min) is between that in the only two reported human laryngeal transplants: At 48 h, we observed a small decrease in expression of MHC-II and lymphocyte-associated molecules, while there was a small increase in other myeloid-associated molecules. This is consistent with the observations of Friedman et al [23] using heterotopic grafts in rats, where separate labelling of donor and recipient cells suggested depletion of donor leucocytes from the graft before the appearance of recipient cells.…”
Section: Quantitative Immunofluorescence Immunohistochemistrysupporting
confidence: 93%
“…Previous studies in pigs have suggested that CD163 + CD172 + cells in blood up-regulate surface MHC-II and differentiate effectively into dendritic cells [24] and the MHC-IIand MHC-II + subsets may represent monocytes/ macrophages and immature dendritic cells, respectively [25]. The similarity to the results of Friedman et al [23] is striking. In both allograft and fully matched rat models, these authors found a significant increase in OX62 + cells, both with and without MHC-II co-expression, between days 5-7: again the strongest effect was seen in the subglottis.…”
Section: Quantitative Immunofluorescence Immunohistochemistrysupporting
confidence: 71%
See 2 more Smart Citations
“…Here, we present functional, vascular and myologic observations at 48 h and 1 week after transplantation at which time points we expected to see immune responses to ischaemia–reperfusion injury and to the onset of rejection, respectively [22]. The immunological response of the laryngeal mucosa to transplantation is reported separately.…”
Section: Introductionmentioning
confidence: 99%